The family status, static and dynamic identity of the child and his integration to its biological family as rights of the son in the challenge of paternity process - Saravia Quispe, José Yván (2018)
The purpose of this article is to analyze the rights that reach the child or adolescent when they are immersed in a process of challenge of paternity, in this way, seeks to define the regulatory context established in the irrevocability and expiration of the denial of recognition of filiation, established in articles 395º and 400º of the civil code. Likewise, the right to the child’s identity will be analyzed, both in its static aspect and in the dynamics and the right to be integrated to its biological family, with the purpose of understanding with greater amplitude the invoked rights and being able to make a correct weighing before an evident collision of principles; searching in response what most benefits the child or adolescent.